Potencial de uso de fibras de Schizolobium parahyba (Vell.) Blake na preparação de compósitos de polipropileno - Silva, Juliette Pereira da (Universidade Federal de São Carlos, 2018)
The use of plant fibers as reinforcement of thermoplastic polymers in recent years has aroused great worldwide interest, since natural fibers offer economic, processing and environmental advantages. In this context, the objective of this study was to evaluate the properties of wood and fibers of Schizolobium parahyba (Vell.) Blake at early age, from experimental planting, as reinforcement of polypropylene (PP) matrix composites. The basic density, cellulose content, hemicelluloses, lignin, extractives and ashes, as well as the fiber size and microfibril angulation of the wood of four guapuruvu trees (A1, A2, A3 and A4) were determined. Then, the mechanical behavior of reinforced polypropylene matrix composites with different fiber contents was evaluated in order to establish their relation between the characteristics of the wood and the fibers. The contents of guapuruvu fibers used were 0; 20 and 30% by mass and the compatibilizing agent was 2%. The composites were prepared in a co-rotational double-threaded extruder. The extrudate compositions were granulated and then injection molded. The basic density of guapuruvu ranged from 0.237 g.cm-³ to 0.243 g.cm-³, with a clear tendency to reduce wood density with tree height. Regarding the anatomical characteristics, there were no variations in the results of fiber length, fiber width and lume diameter among the different trees studied. The wall thickness of the fibers was higher in samples A1 and A2 and the angle of microfibrils was higher in A3 and lower in A2. In addition, there was no statistical difference in the results of aspect ratio among the trees. Regarding the chemical composition, there were no variations in the results for lignin, cellulose, hemicelluloses and extractives among the studied trees. As for ash, the highest concentration was found in A1 and the lowest in A2 and A3. The results showed that the tensile strength increased with the percentage increase of fibers for all samples, except for sample A1, where tensile strength values were similar in the compositions of 20% and 30%. Similarly, the modulus of elasticity also increased with the addition of fibers in all samples, and this effect was more pronounced for the 30% percentage of guapuruvu fiber. Already the elongation at the break decreased in comparison to the pure PP and with the percentage increase of fibers. The Izod impact strength values of the composites did not change significantly in relation to the pure polymer By the results obtained it can be deduced that the guapuruvu fibers from native species, rapid growth, easy adaptation, which has a low density wood can be used as filler in PP composites, exerting a reinforcing action. Having the composite prepared with 30% by weight guapuruvu fibers and 2% Polybond 3200 presented better properties.
Potential use of Schizolobium parahyba (Vell.) Blake fibers in the preparation of polypropylene composites
Keywords: Guapuruvu; Fibras vegetais; Compósitos poliméricos; Reforço; Vegetable fibers; Polymer composites; Reinforcement; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::TECNOLOGIA E UTILIZACAO DE PRODUTOS FLORESTAIS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS